Decoding estrogen receptor and GPER biology: structural insights and therapeutic advances in ERα−positive breast cancer - Saha, Taniya; Lukong, Kiven Erique (Frontiers in Oncology, 2025)
Classical estrogen receptors, ERα and ERβ, along with the membrane-bound G-protein-coupled estrogen receptor (GPER), play critical roles in driving ERα−positive breast cancer (BC). Clinical management of this subtype relies on endocrine therapy (ET), which targets ER signaling through selective estrogen receptors modulators (SERMs), degraders (SERDs), and aromatase inhibitors (AIs). While ET has significantly reduced recurrence and mortality rates, acquired resistance remains a major therapeutic challenge. Activating ESR1 mutations, which encode constitutively active ERα variants, are detected in 30-50% of therapy-resistant metastatic ERα−positive BC and serve as emerging biomarkers of poor prognosis. These hot-spot mutations stabilize ERα in its agonist conformation, thereby enabling ligand-independent transcriptional activation. Understanding the conformational constraints that keep wild-type ERα in an “off-state” in the absence of ligand—and how activating ESR1 mutations disrupt these regulatory mechanisms—is critical for developing effective targeted therapies. Concurrently, GPER-mediated non-genomic signaling, often inadvertently activated by SERMs and SERDs, contributes to tamoxifen resistance. This review explores the structural and functional intricacies of ERα, the impact of ESR1 mutations on its ligand-binding domain (ERα−LBD) and their contribution to ET resistance, and the role of GPER-mediated signaling in ERα−positive BC. We further highlight recent advances in next-generation therapeutics targeting both ERα mutants and GPER, which may offer a more effective, integrated strategy to overcome ET resistance.